Disturbance and noise rejection controller design for smooth takeoff / landing and altitude stabilization of quad-rotor - M. Hassan, Tanveer (American-Eurasian Network for Scientific Information (AENSI), 2014)
Link to publisher's homepage at http://www.aensiweb.com